Evaluating the Lisbon strategy - Oliver Treidler (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2011)
The Lisbon Strategy (hereafter LiS) was formally introduced by the special European Council in Lisbon in March 2000. European leaders adopted this strategy with the objective of turning the EU into "…the most dynamic and competitive knowledge economy in the world capable of sustainable economic growth with more and better jobs and greater social cohesion and respect for the environment". This strategy constituted the blueprint for European economic policymaking from 2000 to 2010. Since its inception the LiS has been the subject of numerous publications and debates. Yet, surprisingly it has never been subjected to a detailed evaluation. Most publications merely evaluate selected aspects or annual progress, ultimately remaining inconclusive. The immediate added value of this paper is the provision of a more consistent and convincing answer to the question "Was the Lisbon Strategy successful?". It will be demonstrated that vital questions have remained unanswered and that many potential lessons have never been learned. Consequently, the successor strategy of the LiS, the so-called "Europe 2020" strategy, is condemned to repeat past mistakes. Contemporary discussions, such as "Europe 2020 a promising strategy?" (Intereconomics, Volume 45, Number 3, May/June 2010), exhibit an untoward optimism regarding Europe 2020. Documenting the failure of the LiS, this paper illustrates the need to critically reassess the merit of Europe 2020. The first section presents a concise analysis of the most popular evaluations - identifying the main caveats. Addressing these caveats, the second section outlines a new assessment framework for evaluating the success of the LiS. In the third section the framework is applied. The fourth section concludes by discussing unanswered questions.
Keywords: 330